2021
DOI: 10.1074/jbc.ra120.016506
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic thick filaments: A new avenue for better understanding the myosin super-relaxed state in healthy, diseased, and mavacamten-treated cardiac systems

Abstract: A hallmark feature of myosin-II is that it can spontaneously self-assemble into bipolar synthetic thick filaments (STFs) in low ionic strength buffers, thereby serving as a reconstituted in-vitro model for muscle thick filament. While these STFs have been extensively used for structural characterization, their functional evaluation has been limited.  In this report, we show that myosins in STFs mirror the more electrostatic and cooperative interactions that underlie the energy-sparing super-relaxed (SRX) state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 67 publications
(144 reference statements)
12
70
0
Order By: Relevance
“…This result inferred that the mechanism of action of RLC phosphorylation is the increase in Huxley's N a parameter, which is consistent with a reduction of SRX and increase in DRX myosin states (Craig et al, 1987;Nag et al, 2017;Toepfer et al, 2016b). This has recently been validated in a synthetic thick filament system (Gollapudi et al, 2020). In addition phosphorylation of cRLC leads to a higher power production and V max in trabecular muscle (Toepfer et al, 2013), inferring that cRLC phosphorylation is central to adapting sarcomeric power, which is at least partly mediated by altering IHM interactions.…”
Section: Introductionsupporting
confidence: 68%
“…This result inferred that the mechanism of action of RLC phosphorylation is the increase in Huxley's N a parameter, which is consistent with a reduction of SRX and increase in DRX myosin states (Craig et al, 1987;Nag et al, 2017;Toepfer et al, 2016b). This has recently been validated in a synthetic thick filament system (Gollapudi et al, 2020). In addition phosphorylation of cRLC leads to a higher power production and V max in trabecular muscle (Toepfer et al, 2013), inferring that cRLC phosphorylation is central to adapting sarcomeric power, which is at least partly mediated by altering IHM interactions.…”
Section: Introductionsupporting
confidence: 68%
“…1C and Table 1). IC50 values reported for mavacamten, and blebbistatin in this study are consistent with those reported in the literature (21,25,26,28,29,38).…”
Section: Activitysupporting
confidence: 92%
“…3A. The relative SRX population increased gradually with increasing mavacamten concentration, reaching 100% at 3.25 μM, suggesting that mavacamten shifted the myosin DRX-SRX equilibrium more towards the SRX state, consistent with what has been observed earlier (23,25,26). The concentration of mavacamten required to attain a half-maximal increase of myosin population in the SRX state is 1.21±0.35 μM, close to the IC50 of ATPase data measured in various systems (Table 1).…”
Section: Binding Of Mavacamten To a Different Site On Myosin Than Of supporting
confidence: 85%
See 1 more Smart Citation
“…This report is discussed further under section ‘Diseased state and therapeutic modulators of myosin SRX state ’. In reconstituted full-length porcine cardiac myosin thick filaments, it has also been recently reported that either phosphorylation of the RLC with MLCK or depletion of RLC decreases the myosin population in the SRX state ( Gollapudi et al, 2020a ). All of these observations together suggest an RLC phosphorylation-mediated shift in DRX↔SRX state equilibrium toward the DRX state of myosin.…”
Section: Muscle Physiology and The Myosin Srx Statementioning
confidence: 98%